The European Context of the Group Insurance Contract - Fras, Mariusz (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The entirety of norms on the relations connected with conclusion and performance of insurance contracts make up economic insurance law. Because of its objective homogeneity, it is generally treated as a separate branch of law. From the dogmatic perspective, its permanent element are group insurance contracts. However, the results of a comparative law research allow to draw the conclusion that in a substantial number of legal systems the term “group insurance” is not to be found in normative acts. In the literature, multiple attempts were made to expound the legal nature of the group insurance contract. Still, there is no consensus as to the nature of the legal relationship arising from conclusion of a group insurance contract. The article concerns the proposal of normative regulation of group insurance contract.